CRITICAL THINKING SKILLS PROFILE OF JUNIOR HIGH SCHOOL STUDENTS IN HUMAN RESPIRATION SYSTEM MATERIALS - Nuriyah, Tutut Sinta; Hayati, Nur (NUKLEO SAINS : JURNAL PENDIDIKAN IPA, 2023)
Critical thinking skills were indispensable in the 21st Century in activities to solved problems to finded solutions. The aims of this study was to determined the profile of critical thinking skills of students of SMP X Jombang in the subject of the human respiratory system. This type of research used descriptive qualitative. The subjects of this research were students of SMP X Jombang with a total of 20 students. The research instrument used critical thinking questions that had been validated by the validator. The critical thinking measurement rubric uses a range of indicators 0-5. Data on critical thinking tested results were analyzed using a descriptive method that described students' critical thinking abilities. The results of this research indicated that the level of critical thinking skills of students of SMP X Jombang was in the range of indicator 3 with well developed criteria. The percentage obtained is 60% with well-developed criteria, 40% with underdeveloped criteria.